Virtual pedophilia : sex offender profiling and U.S. security culture - Harkins, Gillian (Duke University Press, 2020)
"VIRTUAL PEDOPHILIA examines the cultural construction of the pedophile in relation to the rise of the carceral state and neoliberal tactics of forensic securitization. The pedophile, according to Gillian Harkins, is everywhere and nowhere: he eludes diagnostic and forensic profiling by slipping into the veneer of everyday normality. But it wasn't always this way; in this book, Harkins investigates the changing discourses of pedophilia over the late twentieth and early twenty-first centuries to ask why and how the pedophile shifted from a social outcast to the image of white male normality, and why the latter image of the pedophile became a cultural fixation. According to Harkins, this shift was also accompanied by new security regimes: now that the pedophile could no longer be easily detected, the point was to detect potential crime through constant vigilance. Drawing on film, television, and popular culture, Harkins explores how the everyday American was inscripted to "hunt" white male pedophiles, arguing that these cultural texts implied the state and science were no longer sufficient to find the pedophile, thereby creating a biopolitics in which everyone must be on the lookout. Drawing on a Deleuzian interpretation of virtuality as potentiality, as well as the contemporary understanding of virtuality as a condition of technologically produced reality, Harkins positions the pedophile as a virtual construction: an always possible potential whose actuality needs to be determined using modern technologies and security apparatuses. In chapters 1 and 2, Harkins outlines a genealogy of the pedophile from Krafft-Ebings's naming of "paedophilia erotica" in 1886 to today's construction of the virtual pedophile. Chapter 3 focuses on the cultural production of the pedophile by examining the television series Law and Order: Special Victims Unit and To Catch a Predator, and how these shows trained audiences to "detect" pedophiles. Chapter 4 examines the pedophile in documentary and narrative film. In the final chapters, Harkins turns towards queer encounters with the security regimes around pedophilia and sex offenders, and considers what's at stake in the calls to dismantle or reduce sex offender management. This book will be of interest to students of gender and sexuality studies, neoliberalism, carceral studies and the security state, cultural studies, and social theory"--